The murine gammaherpesvirus-68 gp150 acts as an immunogenic decoy to limit virion neutralization. - Laurent Gillet; Janet S May; Susanna Colaco; Philip G Stevenson (PLoS ONE)
Herpesviruses maintain long-term infectivity without marked antigenic variation. They must therefore evade neutralization by other means. Immune sera block murine gammaherpesvirus-68 (MHV-68) infection of fibroblasts, but fail to block and even enhance its infection of IgG Fc receptor-bearing cells, suggesting that the antibody response to infection is actually poor at ablating virion infectivity completely. Here we analyzed this effect further by quantitating the glycoprotein-specific antibody response of MHV-68 carrier mice. Gp150 was much the commonest glycoprotein target and played a predominant role in driving Fc receptor-dependent infection: when gp150-specific antibodies were boosted, Fc receptor-dependent infection increased; and when gp150-specific antibodies were removed, Fc receptor-dependent infection was largely lost. Neither gp150-specific monoclonal antibodies nor gp150-specific polyclonal sera gave significant virion neutralization. Gp150 therefore acts as an immunogenic decoy, distorting the MHV-68-specific antibody response to promote Fc receptor-dependent infection and so compromise virion neutralization. This immune evasion mechanism may be common to many non-essential herpesvirus glycoproteins.